Financial incentives and educational investment: The impact of performance-based scholarships on Student time use - Lisa Barrow; Cecilia Elena Rouse (Federal Reserve Bank of Chicago, 2013)
Using survey data from a field experiment in the U.S., we test whether and how financial incentives change student behavior. We find that providing post-secondary scholarships with incentives to meet performance, enrollment, and/or attendance benchmarks induced students to devote more time to educational activities and to increase the quality of effort toward, and engagement with, their studies; students also allocated less time to other activities such as work and leisure. While the incentives did not generate impacts after eligibility had ended, they also did not decrease students' inherent interest or enjoyment in learning. Finally, we present evidence suggesting that students were motivated more by the incentives provided than simply the effect of giving additional money, and that students who were arguably less time-constrained were more responsive to the incentives as were those who were plausibly more myopic. Overall these results indicate that well-designed incentives can induce post-secondary students to increase investments in educational attainment.
Keywords: 330; Education